2022
DOI: 10.2147/cmar.s346976
|View full text |Cite
|
Sign up to set email alerts
|

Novel Nomogram Based on Inflammatory Markers for the Preoperative Prediction of Microvascular Invasion in Solitary Primary Hepatocellular Carcinoma

Abstract: Purpose We aimed to develop and to validate a novel nomogram based on inflammatory markers to preoperatively predict microvascular invasion (MVI) in patients with solitary primary hepatocellular carcinoma (HCC). Patients and Methods Data from 658 patients with solitary primary HCC who underwent hepatectomy at the First Affiliated Hospital of Zhengzhou University from June 2018 to October 2021 were retrospectively analyzed. Patients were divided into training (n=441) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The recruited population were from China in ten publications, from Japan in two publications, from Austria in one publication, and from America in one publication. HCC patients received hepatectomy in six studies [ [21] , [22] , [23] , [30] , [31] , [32] ], interventional therapies in three studies [ 24 , 29 , 34 ], and mixed therapies in other studies. The cut-off of PLT ranged from 100ⅹ10 9 /L to 222ⅹ10 9 /L.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recruited population were from China in ten publications, from Japan in two publications, from Austria in one publication, and from America in one publication. HCC patients received hepatectomy in six studies [ [21] , [22] , [23] , [30] , [31] , [32] ], interventional therapies in three studies [ 24 , 29 , 34 ], and mixed therapies in other studies. The cut-off of PLT ranged from 100ⅹ10 9 /L to 222ⅹ10 9 /L.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies with a total of 8759 HCC patients reported the effect of PLT on VI. According to the types of VI, MVI were recorded in seven studies [ 22 , 23 , 27 , 28 , [30] , [31] , [32] ], PVTT in two studies [ 26 , 29 ], and any VI in two studies [ 21 , 25 ]. Meta-analysis demonstrated that, there was a significantly elevated risk of VI in patients with a high level of PLT (11 studies, 8759 patients; OR = 1.44, 95%CI: 1.02–2.02) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the AUC of another nomogram was 0.839 (n = 627 HCCs, single center), lacking calibration, validation data and external validation. 19 Furthermore, Gu et al 20 developed a model for predicting MVI based on seven features without external validation (n = 658 HCCs, single center), and the AUCs in training and validation set were 0.788 and 0.735, respectively. Meanwhile, Tang et al 45 also developed a nomogram (n = 273 patients, single center), with an AUC of 0.754 in training set and an AUC of 0.746 in validation set.…”
Section: Discussionmentioning
confidence: 99%
“…The conclusions drawn between different studies are also inconsistent, and the best cutoff values are also different. [18][19][20] In addition, some previous studies have suggested that aminotransferase-to-platelet ratio (APRI) [21][22][23] and gamma-glutamyl transferase-to-platelet ratio (GPR) [24][25][26] are independent risk factors for shorter survival and higher recurrence after HCC surgery. However, it is still uncertain whether preoperative APRI or GPR can predict MVI in solitary HCC, and there is no report on the relationship between APRI/GPR and MVI.…”
Section: Introductionmentioning
confidence: 99%
“…The collected pathological results show that the tissue structures of the normal tissue and tumor tissue are different, as shown in Figure 10. relationship between specific molecular markers of liver cancer and its treatment and prognosis (25)(26)(27). However, there is no relevant previous research on an RBP prognostic model of liver cancer.…”
Section: Verification Of the Expression Level In The Hpa Databasementioning
confidence: 99%